The cultural life of money - Gil, Isabel Capeloa; Silva, M. Helena Gonçalves da (Culture & conflict, 2015)
The book discusses how culture simultaneously shapes and is shaped by the economy. Over the past few years, as the world has staggered from one financial crisis to another, the neat separation of economics and culture has been consistently challenged. To understand the current state of affairs, it has become increasingly necessary to understand the conjuncture that rules the production of value in economic systems, how money shapes social relations and affects discursive practices. By discussing the vocabulary, by understanding the rhetoric and interpreting the narratives, be it of crisis, austerity, growth, welfare, neo-liberalism or socialism, new modes of imaging the economic system may be made possible. The book is structured in four chapters dealing with theory and conjuncture (“Philosophies of Money”), with the visual arts and investment (“The Arts and Finance”), with literary representation and narrativity (“Literature and Money Matters”) and with the cognitive impact of fiduciary representation (“Cognitive Moneyscapes”). This collection analyses the process whereby a material icon invested with the symbolical power to rule social exchange becomes an explanatory narrative determining the way societies produce meaning